The Practical Aspects of Allergen Management in Meat Manufacturing in the United Kingdom - Sikora, Ewa; Górna, Justyna (Studia Oeconomica Posnaniensia, 2017)
Food allergies can cause unusual reactions from the immune system which presents incidences of various clinical symptoms. The symptoms have the same character and occur always after eating food of which the person is allergic to. Allergens can be vegetable protein molecules or of animal origin. Food manufacturers have legal requirements to inform customers on labels about all allergens present in any product offered for sale. While in the case of allergen-free products they have to make every effort to avoid cross contamination with allergens which are present in meat factories. The proper management of allergens has the benefit of allowing a company to avoid losses relating to the withdrawal of the product from the market; loss of position in the industry and reduces the risk of having to defend cases in UK courts. The context of this article is the study of the legal regulations and voluntary standards introduced by a company. The aim of this article is to discuss the most important factors for the successful management of allergens by the example of a meat manufacturer in the UK. A group of these factors include food labelling, employee training, risk analysis of cross contamination, audits and the checks of suppliers, validation and verification of the cleaning process and the process of new products in development. The second part of the article is a detailed research into the issue that such a large number of hospitalizations (4,500) and deaths (10) from food allergies still occur every year in the UK, despite all the safety procedures and legislation that is currently in force. These numbers indicate that the legal regulations and the requirements of voluntary standards must continue to improve the management of allergens in food manufacturing.